Addendum to the paper 'Nonsmooth DC-constrained optimization: constraint qualification and minimizing methodologies'. (2nd November 2022) - van Ackooij, W.; de Oliveira, W.
Abstract : In this addendum to our paper published in [Optim. Meth. Softw. 34(1) (2019), pp. 890–920], we provide more details concerning Proposition 2.1 figuring therein. The original proposition implicitly assumed that the constraint mapping was Clarke-regular. Here, not only do we fix some inaccuracies and confusing statements in Section 2 of that paper, but we also provide an extension of our previous results well beyond that setting.